Analysis of miRNA profile in circulating extracellular vesicles of patients with pulmonary arterial hypertension. (10th June 2022) - Khandagale, A; Corcoran, P; Nikpour, M; Siegbahn, A; Christersson, C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Swedish Research Council Introduction: Pulmonary arterial hypertension (PAH) is characterized by a progressive elevation of pulmonary pressure leading to right ventricular dysfunction and is associated with a poor prognosis. Patients with PAH have increased numbers of circulating extracellular vesicles (EVs), which are small membrane vesicles (<1 µm) released from different cells. EVs contain surface antigens, proteins and genetic material, and serve as vectors of intercellular communication. MicroRNAs (miRs) are small RNAs that act as post-transcriptional regulators inhibiting gene expression. Alteration of miR expression is associated with stage, progression and severity of different diseases making them suitable as potential biomarker. The aim of the study was to evaluate the miRNA profile contained in EVs derived from plasma of both control healthy subjects and patients with PAH. Methods: Circulating EVs, purified from platelet free plasma, from 9 healthy controls (HC) and 10 PAH patients were analyzed. After total RNA isolation, fixed volumes of total RNA were biotinylated to generate fragmented cRNA. Samples were then subjected to Microarray analysis using GeneChip miRNA 4.0 Array. Data was further analysed using various bioinformatics tools. Results: Total of 762 miRs were identified while comparing PAH vs HC groups, of which 22 were found to be down-regulated and 3 were up-regulated in PAH group (Table 1). Gene ontology enrichment analysis revealed various cell signaling pathways where-in identified miRs are involved. Conclusions: PAH patients pack and transport a differentiated expression profile of miRs, suggesting that EVs might serve as signaling vectors. Further analyses of the functionality of EVs' miRs is currently undergoing in our lab to understand its role during PAH progression and/or inhibition.